2000
DOI: 10.1212/wnl.55.2.218
|View full text |Cite
|
Sign up to set email alerts
|

A milestone for normal development of the infantile brain detected by functional MRI

Abstract: A rapid inversion of response revealed by fMRI with photic stimulation in infants suggests a change in oxygen consumption during neuronal activation, which is related to rapid synapse formation and accompanying increased metabolism. fMRI can detect dynamic metabolic changes during brain maturation, which is a different developmental process from white matter myelination. The metabolic changes detected by fMRI provide a milestone for the evaluation of normal brain development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 27 publications
6
57
1
3
Order By: Relevance
“…Language, motor and visual fMRI studies in children under 5 years showed age-related BOLD responses (Martin et al, 1999). Whereas awake adults showed consistent occipital positive BOLD responses to visual stimulation (Belliveau et al, 1991), children presented either positive or negative BOLD changes, depending on their age (Morita et al, 2000;Yamada et al, 2000;Marcar et al, 2004). However, normal children above eight years have showed no differences compared to adults in sensory and cognitive studies (Casey et al, 1997;Thomas et al, 1999).…”
Section: Hrfs Correlation With Agementioning
confidence: 97%
See 1 more Smart Citation
“…Language, motor and visual fMRI studies in children under 5 years showed age-related BOLD responses (Martin et al, 1999). Whereas awake adults showed consistent occipital positive BOLD responses to visual stimulation (Belliveau et al, 1991), children presented either positive or negative BOLD changes, depending on their age (Morita et al, 2000;Yamada et al, 2000;Marcar et al, 2004). However, normal children above eight years have showed no differences compared to adults in sensory and cognitive studies (Casey et al, 1997;Thomas et al, 1999).…”
Section: Hrfs Correlation With Agementioning
confidence: 97%
“…In early fMRI studies in children, it has been hypothesized that age-related increases in oxygen consumption are due to changes in synaptic density or to high-energy consumption by ineffective recruitment of synapses or the presence of superfluous synaptic connections (Huttenlocher, 1979;Yamada et al, 2000;Marcar et al, 2004). As a result, higher levels of deoxyhemoglobin following an event are expected in very young children.…”
Section: Hrfs Correlation With Agementioning
confidence: 99%
“…Born et al [1996Born et al [ , 1998 reported that flickering light stimulation induced a signal decrease in the occipital region in infants, which is different from the signal increase in adults, and that the localization of the activation was age-dependent. Furthermore, Yamada et al [1997Yamada et al [ , 2000 reported an inverse response in infants that is related to a developmental process of white matter myelination.…”
Section: Introductionmentioning
confidence: 99%
“…A more accurate measure of the changes in myelination that accompany increases in development is needed, one that relies less on qualitative judgments and more on a quantitative measure. Such attempts have been made looking at myelination [18,19]. Quantitative analyses of white matter myelination in the visual pathways were performed using MRI, and a positive relation was found between age and myelination development in the proximal optic radiation and the distal optic radiation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such attempts have been made looking at myelination [18,19]. Quantitative analyses of white matter myelination in the visual pathways were performed using MRI, and a positive relation was found between age and myelination development in the proximal optic radiation and the distal optic radiation [18]. However, for asphyxiated infants, the qualitative judgment was more predictive of neurodevelopmental outcome than was the quantitative assessment [19].…”
Section: Introductionmentioning
confidence: 99%